Gambaran Pemetaan Faktor Risiko Stunting Pada Balita Stunting di Desa Ampadi Kabupaten Landak Tahun 2023 - Sitepu, Rika Mandasary; Suwarni, Linda; Selviana (Avicenna: Jurnal Ilmiah, 2024)
Backgorund: Stunting incidence in Indonesia is 21.6% which is still quite high compared to the target in 2024 of 14%. Primary prevention efforts are essential in reducing the number of stunts through mapping stunting risk factors for stunting in stunted toddlers so that intervention programs can be carried out as a stunting prevention effort. Objective: This study aims to map the risk factors for stunting incidence in stunted toddlers in Ampadi Village, Landak Regency. Method: This research includes observational research with a descriptive approach. The population of this study were all stunted toddlers in 2023 in Ampadi Village, Landak Regency, which amounted to 68 people.  The sample of this study used total sampling. Data analysis using univariate by describing risk factors in the form of percentages and in the form of mapping. Result: The results shows the prevalence of stunting reached 45.9%, with Nabo Hamlet having the highest prevalence (18.2%). The main risk factors identified were maternal age <20 years, not exclusively breastfeeding, early complementary feeding, incomplete immunization, and LBW. Dusun Nabo had the highest percentage for almost all risk factors. Conclusion: It is concluded that comprehensive and contextual interventions are urgently needed to address the stunting problem in Landak Regency. Keywords: Prevention Model, Local Wisdom, Stunting, Mapping Stunting Risk Factor